Inhibition by normal human serum of Mycobacterium avium multiplication in cultured human macrophages. - Crowle, A J (1989)
Normal human serum used as a protein supplement in RPMI 1640 medium inhibited growth in blood-derived human macrophages (MP) of virulent Mycobacterium avium serovars 4 and 8, derived from patients with acquired immunodeficiency syndrome, but not virulent Mycobacterium tuberculosis. A defined serum substitute (SS) promoted the intramacrophage growth of M. avium but not of M. tuberculosis. The effects of serum or SS were measured by counting viable bacteria in lysates of the MP at 0, 4, and 7 days after their infection by the bacteria. Neither serum nor SS inhibited or enhanced M. avium growth in the absence of MP. The results suggest that a nutrient essential for intracellular replication of M. avium is made by MP from a pronutrient present in both SS and serum and that something in serum inhibits MP conversion of the pronutrient to nutrient. This inhibition may be an important mechanism of native resistance against M. avium in normal people.